Two-photon fluorescent probes for quantitative bio-imaging analysis in live tissues - Juvekar, Vinayak; Lee, Hyo Won; Lee, Dong Joon; Kim, Hwan Myung (TrAC - Trends in Analytical Chemistry, 2022)
Two-photon (TP) microscopy (TPM) is an indispensable visualization tool for deep-tissue imaging. TPM uses the low energy light of the near-infrared window as an excitation source of fluorophores which reduces autofluorescence, photodamage, and light scattering, resulting in high resolution fluorescence images potentially beyond several millimeter depths in living systems. Due to the continuous development of the microscope and advances in optical output algorithms, it is crucial to develop innovative strategies for the quantitative analysis of biomedically relevant target analytes in living systems using TP fluorescence probes. In this review, we have highlighted ratiometric TP probe design strategies with representative ratiometric TP sensors in the last decade. We have also summarized the recent progress in the development of TP probes published between 2017 and 2022 for quantitatively detecting analytes such as enzymes, reactive species, bio-thiols, pH, neutral molecules, and metal ions in live cells and tissues.
Keywords: Bio-imaging; Fluorescent probes; Imaging analysis; Live tissue; Living systems; Ratiometric; Tissue imaging; Two photon; Two photon microscopy; Two-photon probes; Bio-imaging; Quantitative analysis; Tissue imaging; Two-photon microscopy; Two-photon probes